2017
DOI: 10.1159/000475529
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Heterogeneity in Endometrial Carcinoma: Practical Consequences

Abstract: Endometrial carcinoma (EC) shows intertumor heterogeneity, with several different histologic types differing in their morphologic and molecular features. There is also intratumoral morphologic heterogeneity, with different neoplastic cell components within the same tumor, with different morphologic and molecular features. In this article, we discuss the consequences of tumor heterogeneity in EC at the morphologic and molecular levels, by describing some illustrative examples produced by the research team. They… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 17 publications
0
21
0
Order By: Relevance
“…High frequency of POLE, PTEN, CTNNB1, PIK3R1, ARID1A, KRAS mutations and microsatellite instability are found in type I tumors, whereas mutations in TP53 and FBXW7, and somatic copy number alterations are more frequently found in type II carcinomas (9, 10). Coenegrachts et al found that in majority of the cases, SC and EEC components in mixed EEC-SC exhibit distinct molecular characteristics, but have similar mutation profiles compared to SC and EEC cancers, respectively (11,12). In the present case with mixed histological components, frequently mutated genes in endometrioid tumors (PTEN, ARID1A, KRAS) and serous tumors (TP53, FBXW7) are all mutated.…”
Section: Discussionmentioning
confidence: 47%
“…High frequency of POLE, PTEN, CTNNB1, PIK3R1, ARID1A, KRAS mutations and microsatellite instability are found in type I tumors, whereas mutations in TP53 and FBXW7, and somatic copy number alterations are more frequently found in type II carcinomas (9, 10). Coenegrachts et al found that in majority of the cases, SC and EEC components in mixed EEC-SC exhibit distinct molecular characteristics, but have similar mutation profiles compared to SC and EEC cancers, respectively (11,12). In the present case with mixed histological components, frequently mutated genes in endometrioid tumors (PTEN, ARID1A, KRAS) and serous tumors (TP53, FBXW7) are all mutated.…”
Section: Discussionmentioning
confidence: 47%
“…EC is the most frequent of the malignant tumors of the female genital tract with an important intertumoral heterogeneity, depending on histological and molecular types, and also intratumoral, due to the different cell components within the same tumor [ 32 , 33 ]. The study of the protein expression profile of EC, including the study of ectonucleotidases, contributes to the improvement of the diagnosis and tumor staging and, in consequence, the clinical management of patients [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…As all known, the substantial and disorder cell populations is an essential pathological characteristic of most malignant tumors, so the diffusion rate of water molecules is significantly slow in malignancies and they are always hyperintense on DWI. The heterogeneity is another important pathological feature of cancer, multi-region sequencings performed in many carcinomas including endometrial cancer, breast, lung, colorectal, and renal cancer have uncovered heterogeneity exists in all cancer types [22][23][24][25][26][27]. The heterogeneity may lead to different diffusion rate of water.…”
Section: Discussionmentioning
confidence: 99%